Lo spazio pubblico nella seconda modernità - Spini, Debora (SocietàMutamentoPolitica, 2011)
This essay discusses the crisis of public spaces in the wider perspective of the crisis of politics determined by the paradoxical effects of modernity, which will be identified primarily with the transformations of capitalism and with the unforeseen and un-intentional of scientific and technological progress. Public spaces in contemporary democracies are faced with issues of unprecedented magnitude – such as “global challenges” or “global risks” - whilst witnessing a profound transformation of all traditional political actors. Our public spaces do not seem capable of responding to such momentous challenges, and become increasingly un-political or “sub-political”. Nonetheless,–besides the symptoms of crisis - the conclusion of this essay focuses on all those signals pointing towards a renewal of politics made evident by new forms of political agency on the global level.